Development of multiorganic calciphylaxis during teriparatide, vitamin D, and calcium treatment. Issue 8 (August 2016) - Monegal, A.; Peris, P.; Alsina, M.; Colmenero, J.; Guañabens, N.
Abstract Non-uremic calciphylaxis is a severe rare disorder characterized by ischemic necrosis. Recently, three cases of cutaneous calciphylaxis have been described in the context of teriparatide treatment. We present a 51-year-old woman with alcoholic cirrhosis who developed multiorganic calciphylaxis shortly after starting teriparatide treatment associated with calcium and 25-hydroxyvitamin D supplements for severe osteoporosis. After lengthy care of the infectious complications and treatment with bisphosphonates and sodium thiosulfate progressive improvement was observed over a 3-year period. The time between the initiation of teriparatide and the development of calciphylaxis suggests that this agent may have been the triggering factor of this process. Nevertheless, other non-negligible risk factors for calciphylaxis such as alcoholic liver disease, obesity, and vitamin D treatment must also be considered in this patient. Considering the severity of this extremely rare clinical condition, better knowledge of the risk factors related to calciphylaxis development is mandatory.